Cloning and Sequence Analysis of Capsid Protein Gene of Iridovirus Indonesian Isolates - M. Murwantoko; Christina Retna Handayani; Rarastoeti Pratiwi (Indonesian Journal of Biotechnology, 2009)
Iridovirus was known as agents that caused serious systemic disease in freshwater and marine fishes. The mortality up to 100% of orange-spotted grouper (Epinephelus coioides) due to iridovirus infection has been reported in Indonesia. The gene encoding capsid protein of iridovirus is supposed to be conserved and has the potency for the development of control methods. The objectives of this study are to clone the gene encoding capsid protein iridovirus and to analyze their sequences. The   spleen tissues of orange-spotted grouper were collected and extracted their DNA. The DNA fragment of capsid protein of iridovirus genes were amplified by PCR using designed primers with the extraction DNA as templates. The amplified DNA fragments were cloned in pBSKSII and sequenced.  The genes encoding capsid protein of iridovirus from Jepara and Bali were successfully amplified and cloned. The Jepara clone (IJP03) contained complete open reading frame (ORF) of the gene composed by 1362 bp nucleotides which encoded 453 amino acids. Those Jepara and Bali (IGD01) clones shared 99.8% similarity in nucleotide level and 99.4% at amino acid level. Based on those sequences, Indonesian iridovirus was belonged to genus Megalocystivirus and shared 99,6-99,9% similarity on nucleotide level with DGIV, ISKNV, MCIV, and ALIV